Folk music of the khmer ethnic group in southern Vietnam: A literature review - Khanh, Pham Tiet (Research Journal in Advanced Humanities, 2026)
This article reviews the research on folk music of the Khmer ethnic group in Southern - Vietnam. The studies on Khmer folk music by Cambodian, Khmer, and Western authors are also summarised in this article. The results of the literature review show that: (1) Studies on folk music of the Khmer ethnic group in the South Vietnam were carried out after 1975, especially after the Doi Moi period in Vietnam in 1986 in association with the state’s policy on conservation and promotion of traditional art forms of ethnic minorities, however, the publications are mainly in Vietnam; (2) Studies on folk music of Khmer people in Cambodia has been researched and published by Western authors in many specialized scientific journals, but most of these studies do not pay attention to folk music of Khmer people in Southern Vietnam (3) The article also has not found specific studies on the correlation between folk music of Khmer people in Southern Vietnam and folk music of Khmer people in Cambodia.